2017
DOI: 10.1002/jat.3509
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution following 28 day repeated oral administration of aluminum‐based nanoparticles with different properties and the in vitro toxicity

Abstract: The tissue distribution and toxicity of nanoparticles (NPs) depend on their physical and chemical properties both in the manufactured condition and within the biological system. We characterized three types of commercially available aluminum-based NPs (Al-NPs), two rod-type aluminum oxide NPs (Al O , AlONPs), with different aspect ratios (short [S]- and long [L]-AlONPs), and spherical aluminum cerium oxide NPs (AlCeO , AlCeONPs). The surface area was in order of the S-AlONPs > L-AlONPs > AlCeONPs. Very importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…17 NPs may become lodged in tissues, and the high durability and reactivity of some NPs raise concerns of their outcomes in the healthy systems. 18,19 Indeed, at this time, not enough data exist to evaluate the biomedical exposure for most engineered NPs. Some NPs that accumulate in animal tissues may have the ability to easily pass through the cell membranes or cross the blood-brain barrier and attack the cells.…”
Section: Introductionmentioning
confidence: 99%
“…17 NPs may become lodged in tissues, and the high durability and reactivity of some NPs raise concerns of their outcomes in the healthy systems. 18,19 Indeed, at this time, not enough data exist to evaluate the biomedical exposure for most engineered NPs. Some NPs that accumulate in animal tissues may have the ability to easily pass through the cell membranes or cross the blood-brain barrier and attack the cells.…”
Section: Introductionmentioning
confidence: 99%
“…10‐0425) (Supporting information, Figure S1D). As shown in Supporting information, Figure S2, the energy dispersive X‐ray spectroscopy mapping profile of AlCeONPs clearly indicated that the outer sheath was composed of Al 2 O 3 , whereas CeO 2 was present within the Al 2 O 3 (Park et al, ). The Brunauer–Emmett–Teller surface‐area analyzer‐specific surface areas of S‐AlONPs, L‐AlONPs, AlCeONPs and AlOOHNPs, calculated from the N 2 adsorption–desorption isotherms at room temperature (<25°C), were 163.4, 105.9, 24.8 and 10.3 m 2 g –1 , respectively (Supporting information, Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…It is also increased by the presence of the hydroxyl group between two spherical types of Al‐NPs. More importantly, in our 28 day repeated oral toxicity test, we identified that AlCeONPs were Al 2 O 3 ‐coated CeO 2 NPs, but not AlCeO 3 NPs, although they have been sold under the trade name of “AlCeONPs” (Park et al, ). Additionally, in our previous study, cerium oxide NPs (CeONPs) were located surrounding the nuclear membrane at 12 hours after exposure to human bronchial epithelial cells, ultimately leading to cell death (Park, Choi, Park, & Park, ).…”
Section: Discussionmentioning
confidence: 99%
“…Female and male Balb-c mice were acclimated to the environment for 2 weeks prior to the initiation of San Martin-Gonzalez 2012). However, the safety of NPs, especially of those that can be uptaken directly, is a topic of great concern (Park et al 2017;Wassef and Quadro 2011).…”
Section: In Vivo Experimentsmentioning
confidence: 99%